Creating and Managing Value in Indian Management Education. (November 2022) - Salunkhe, Uday; Rajan, Bharath; Natarajan, Sujatha
Stakeholder theory and stakeholder engagement (SE) concepts have been widely used in management and marketing literature. In this study, we extend the SE concept to investigate value creation and management in Indian management education. Specifically, for an Indian management institute, we (a) define value, (b) identify nine value categories in which value can be created and managed, (c) advance a SE approach in creating and managing value, (d) identify and categorize value measures as contiguous and future measures, and (e) recognize the resources and capabilities needed to create and manage value. This is the first study in the Indian context to focus on value creation and management through the SE perspective. We conclude the study by discussing the implications of the proposed value categorizations for an Indian management institute and identifying areas for future research.